What makes for a good nursing handover?. Issue 3 (2nd March 2022) - Stonehouse, David
Abstract : This article discusses the important part that the nursing handover plays in providing quality care to patients and the smooth running of the shift and clinical area. Following an introduction stating exactly what is meant by a handover, the relevant and pertinent parts of the Nursing and Midwifery Council code will then be identified and discussed. The importance of good communication as well as delegation will be discussed, before moving on to identify potential issues to achieving a quality nursing handover and ways to overcome these. Finally, the role of the support worker and nursing associate will be made clear.